Comparative transcriptome analyses of three Gentiana species provides signals for the molecular footprints of selection effects and the phylogenetic relationships - Zhou, Tao; Zhao, Yuemei; Zhou, Lipan; Chen, Xiaodan; Jia, Yun; Bai, Guoqing (Molecular genetics and genomics : MGG, 2023)
Species in Gentiana section Cruciata are important alpine plants with a center of diversity and speciation in Qinghai–Tibet Plateau (QTP), and some of these species are sympatrically distributed in northeastern QTP. Studies on genome features and natural selection signatures of sympatric species in section Crucata have been impeded by a lack of genomic resources. Here, we showed transcript characterizations and molecular footprints of selection effects on G. straminea, G. dahurica and G. officinalis based on the comparative transcriptome. A total of 62.97 Gb clean reads were obtained with unigene numbers per species ranging from 141,819 to 236,408 after assembly. We found that these three species had similar distribution of functional categories in different databases, and key enzyme-encoding genes involved in the iridoids biosynthesis were also obtained. The selective pressure analyses indicated that most paired orthologs between these three species were subject to negative selection, and only a low proportion of the orthologs that underwent positive selection were detected. We found that some positive selected genes were involved in “catalytic activity”, “metabolic process”, “response to stimulus” and “response to stress”. Besides, large numbers of SSR primer pairs with transferabilities were successfully designed based on the available transcriptome datasets of three Gentiana species. The phylogenetic relationships reconstructed based on 352 single-copy nuclear genes provided a rough phylogenetic framework for this genus and confirmed the monophyly of section Cruciata . Our study not only provides insights for the natural selection effects on sympatric Gentiana species, but also enhances future genetic breeding or evolutionary studies on Qinjiao species.